HDL Receptor in Schistosoma japonicum Mediating Egg Embryonation: Potential Molecular Basis for High Prevalence of Cholesteryl Ester Transfer Protein Deficiency in East Asia - Yokoyama, Shinji (Frontiers in Cell and Developmental Biology, 2022)
Schistosomiasis is a life-threatening parasitic disease caused by blood flukes, Schistosomes. The parasites reside in visceral/portal veins of the human hosts, lay eggs to excrete in feces via intestinal tracts, and some of the aberrant eggs plug into the liver via the portal blood flow. Ectopic growth of these eggs cause fatal granulomatosis and cirrhosis of the liver. The parasites ingest nutrients from the host blood plasma by using nonspecific and specific transport via their body surface and alimentary tracts. It is especially important for the female adults to obtain lipid molecules since they synthesize neither fatty acids nor sterols and yet produce egg yolk. LDL receptors have been identified in the body of the Schistosomes but their functions in the parasite life cycle have not clearly been characterized. On the other hand, CD36-related protein was identified in the body and the eggs of Asian blood fluke, Schistosoma japonicum, and characterized as a molecule that mediates selective uptake of cholesteryl ester from the host plasma HDL. This reaction was shown crucial for their eggs to grow to miracidia. Interestingly, abnormal large HDL generated in lack of cholesteryl ester transfer protein (CETP) is a poor substrate for this reaction and therefore CETP deficiency resists pathogenic ectopic growth of the aberrant parasite eggs in the liver. This genetic mutation is exclusively found in East Asia overlapping with the current and historic regions of Schistosoma japonicum epidemic. Thus, this is very likely a specific screening mechanism for high prevalence of CETP deficiency in East Asia.